Implementasi E-Goverment pada Sistem Informasi Pemerintahan Desa Kabupaten Kuningan - Aji Permana; Nugraha, Dadan; Wati, Dyah Puteria (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Kuningan Regency has 361 villages and 32 sub-districts consisting of village officials with their duties and authorities. In this case, village officials have not been recorded in a system, which causes a lot of data on officials that does not match the latest data, so that the DPMD (Dinas Pemberdayaan Masyarakat dan Desa) has difficulty collecting data on village officials such as personal identity, position, education, family data and other supporting data. Apart from data collection on apparatus, each village has institutions such as BPD (Badan Permusyawaratan Desa), LPM (Lembaga Pemberdayaan Masyarakat), PKK (Pemberdayaan Kesejahteraan Keluarga), Karang Taruna, Posyandu, RT/RW data, innovations and legal products which have not been recorded so that the DPMD has difficulty getting these data. The village government information system in this research will assist in managing village government data such as the identity of village officials, BPD, LPM, PKK, Karang Taruna, RT/RW, innovation, legal products to the management of proposed village documents for the purposes of reporting the village financial system which includes photos of the Village APBDesa Baligho, ILPPDrab Baligho, Siskeudes Online Homepage, Siskeudes Online Financial Report and Siskeudes Online RAPBDes. The output of this research is the Kuningan Regency Village Government Information System with users divided into DPMD, District and Village parties with access levels according to their needs.